2016
DOI: 10.1371/journal.pone.0165345
|View full text |Cite|
|
Sign up to set email alerts
|

Photoacoustic Imaging of Cancer Treatment Response: Early Detection of Therapeutic Effect from Thermosensitive Liposomes

Abstract: Imaging methods capable of indicating the potential for success of an individualized treatment course, during or immediately following the treatment, could improve therapeutic outcomes. Temperature Sensitive Liposomes (TSLs) provide an effective way to deliver chemotherapeutics to a localized tumoral area heated to mild-hyperthermia (HT). The high drug levels reached in the tumor vasculature lead to increased tumor regression via the cascade of events during and immediately following treatment. For a TSL carry… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 51 publications
6
45
0
Order By: Relevance
“…This non-responder mouse was treated in an identical fashion and was included in this data set as its oxygenation and QUS/QPA behavior was significantly different from HaT-DOX responders. As reported in our previous study for a larger subset of animals, a 90% regression rate was observed 25 days after HaT-DOX treatment [43].…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…This non-responder mouse was treated in an identical fashion and was included in this data set as its oxygenation and QUS/QPA behavior was significantly different from HaT-DOX responders. As reported in our previous study for a larger subset of animals, a 90% regression rate was observed 25 days after HaT-DOX treatment [43].…”
Section: Resultssupporting
confidence: 86%
“…These animals all responded to the HaT-DOX treatment (as assessed by caliper measurements) and experienced a 2 h post-treatment, 22% drop in oxygenation (as assessed by the sO 2 mode). This drop in oxygenation was present as early as 30 min post-treatment and was sustained for the first 24 h. Tumor oxygenation histograms can be used to quantify changes in blood vessel oxygenation throughout the entire tumor [43]. The early changes in blood vessel oxygenation correlate with treatment response: responders’ sO 2 decreased 30 mins post-treatment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations